ANALISA KEHANDALAN PADA MESIN JOINTLESS DENGAN METODE RELIABILITY CENTERED MAINTENANCE - Puguh Elmiawan (Jurnal Teknologi dan Terapan Bisnis, 2019)
In the production department of the D&K Building plant which serves as a place to assemble tire building materials to become a green tire, there is a jointless machine which functions to install jointless material to be assembled with other materials. The frequency of damage in jointless machine components is still high that causes the high losstime. The high losstime indicates a small value of reliability of the machine. The data needed in this study are damaged engine components, engine failure period, and engine component replacement time. In this study, critical components were analysed. The methods used in this analysis were FMEA, LTA and MTTF. The result of the analysis showed that the bearing is jammed with an average reliability of 49% with an MTTF value of 30 days. Broken bearings value an average reliability of 8.5% to an MTTF value of 56 days. Piping accessories (jointless stopper) the average value of reliability is 52% to an MTTF value of 145 days. The stopper bolt has an average reliability of 50% to an MTTF value of 385 days. The results showed that the determination of the critical component replacement time interval can determine the appropriate maintenance activities on the Jointless machine so that the right RCM decision for the company can be achieved.